Application of the Student Teams Achievement Divisions (Stad) Method in Improving Learning Outcomes of Akhlak Aqidah - Imam Faizin (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2019)
This study aims to determine the increase in student learning achievement in learning the moral creed through the STAD (Student Teams-Achievement Divisions) method. The location of this research was at MTs YMI Wonopringgo with a total of 40 students, 22 boys and 18 girls. The data in this study were obtained from interviews, questionnaires, action observations, and evaluation results. This research was conducted in two cycles. Each cycle is carried out based on the stages: (1) preparing an activity plan, (2) carrying out actions, (3) observing, and (4) analyzing followed by reflection. The results of the study showed that the students' ability to solve questions on the moral creed was increasing. This can be seen from the increase in student achievement through the pre-test, post-test cycle I, and post-test cycle II. This can be seen from the average student pre-test which is 62.03, increasing to 67.55 (post-test cycle I), and increasing again to 76.10 (post-test cycle II). Apart from being able to see the average score of students, the increase in student achievement can also be seen from the learning completeness and the minimum completeness criterion (KKM) set is 75. This can be seen from the results of the pre-test of 40 students who took the test, there were 14 students who have completed their studies and 26 students who have not completed their studies with a learning completeness percentage of 35.00%. In the post test cycle I it increased to 52.50% with 21 students completing and 19 not completing, and it increased again in the post test cycle II to 80% with 32 students completing and 8 not completing. Based on the results of the research above, it can be concluded that learning aqidah morals using the Student Teams-Achievement Division (STAD) model can improve student abilities, increase student activity, and increase student cooperation in completing group assignments. Learning becomes fun so students don't get bored easily.